Utilizing Children's Songs to Develop Vocabulary in Indonesian Language Learning Using Special Teaching Modules - Ari Windi Syopyanti; Iis Ristiani (Raja Zulkarnain Education Foundation, 2025)
Vocabulary is an important element in language skills that influences students' speaking, reading, and writing abilities. However, many students still experience limited vocabulary, thus hindering fluency in communication and comprehension of written texts. Through written texts of children's songs, students can learn language in a fun, contextual, and memorable way. This study aims to describe the use of children's songs as a learning medium in developing vocabulary in Indonesian language learning. This study used a quasi-experimental method. The study took place in the odd semester of the 2025/2026 academic year in grade III of Sindangraja 1 State Elementary School, Sukaluyu Cianjur. Indonesian vocabulary data were collected using a test instrument that was compiled objectively and systematically. Vocabulary data were analyzed using descriptive statistical procedures. The results showed that children's songs were able to improve students' vocabulary mastery through repetition of lyrics, pronunciation, and understanding of word meanings. Thus, children's songs are effectively used as a medium for Indonesian language learning in grade III of elementary school.